2015
DOI: 10.1155/2015/371734
|View full text |Cite
|
Sign up to set email alerts
|

Adipsin Is Associated with Multiple Sclerosis: A Follow-Up Study of Adipokines

Abstract: Background and Objective. The role of adipokines in regulation of immune responses has been recognized, but very little is known about their impact on multiple sclerosis (MS). In this study, we analysed whether the major adipokines are differentially expressed in plasma of patients with different MS subtypes and clinically isolated syndrome (CIS) and explored their association with major disease characteristics. Methods. The levels of adiponectin, adipsin, leptin, and resistin in the plasma of 80 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…A study by Natarajan et al showed that in patients with different subtypes of MS and clinically isolated syndrome, adipsin had a predictive potential as a neurodegeneration biomarker. The obtained data correlated with the disease activity, the Expanded Disability Status Scale, and the volume of changes in magnetic resonance imaging 32. The role of adipokines in the regulation of immune responses in MS was also found in other studies.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A study by Natarajan et al showed that in patients with different subtypes of MS and clinically isolated syndrome, adipsin had a predictive potential as a neurodegeneration biomarker. The obtained data correlated with the disease activity, the Expanded Disability Status Scale, and the volume of changes in magnetic resonance imaging 32. The role of adipokines in the regulation of immune responses in MS was also found in other studies.…”
Section: Discussionsupporting
confidence: 75%
“…The obtained data correlated with the disease activity, the Expanded Disability Status Scale, and the volume of changes in magnetic resonance imaging. 32 The role of adipokines in the regulation of immune responses in MS was also found in other studies. However, very little is known about their effect on MS.…”
Section: Discussionsupporting
confidence: 61%
“…However, recipients of adipsin-deficient, but not leptin or adiponectin-deficient adipose remain resistant to arthritis development [174]. A clinical study in MS patients found a strong association with adipsin levels and neurological disability [175]. It will be important to further analyze the role of adipsin in animal models of autoimmune disease to fully understand whether adipsin is pro-or anti-inflammatory.…”
Section: Adipsin In Autoimmunitymentioning
confidence: 99%
“…Therefore, further studies need to be done to reveal possible implications of other adipokines in such regulation. Especially, the role of adipokines that are reported to be involved in immune response (eg, adipsin, acylation stimulation protein [ASP], serum amyloid A3 [SAA3], and IL‐17D), should be investigated.…”
Section: Discussionmentioning
confidence: 99%